Smooth Points of Orlicz Function Spaces Equipped with S-norm - XU Hao; WANG Junming (Journal of Harbin University of Science and Technology, 2024)
Smooth points are important concepts in Banach space geometry theory, which have important applications in estimation theory, probability theory and other fields. In this paper, firstly the dual norm of Orlicz space endowed with s-norm is introduced by convex model and then the norm attainability of dual norm is discussed. On this basis, the explicit form of support functional for Orlicz space endowed with s-norm is given. Finally, a criterion for smooth points in Orlicz space endowed with s-norm is presented.